The Concept of Dowry According to Imam Al Qurthubi in Tafsir Al Jami' Li Ahkamil Quran (Tafsir Analysis of QS An Nisa Verse 4) - Amilia, Dian Mustika; Zuhri, Ahmad (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
The concept of dowry as a man's obligation to give to a woman allows for opportunities to be criticized, even denied, because it will only be aimed at appearing inferior on one side and superior on the other. So, looking at the concept of dowry from the perspective of the Koran confirms that the concept of the Koran applies in any society and anywhere without looking at the materialistic context. This research uses this method of library research. This research also uses the ijmali method. The ijmali method is a method in which the meaning of the verse is explained concisely and globally but quite clearly. Therefore, researchers used this research based on primary data as the main data in this research, namely Tafsir Al Jami'li Ahkamil Quran by Imam Alqurthubi. The dowry is only given by the prospective husband to the prospective wife, not to other women or anyone else, even if they are very close to her. Other people are not allowed to take it, even the husband himself cannot take it except with his wife's permission. However, if his wife allows it, there is no obstacle for him to wear it. According to Imam Al-Qurthubi, dowry is an absolute right that the prospective wife has. He said that giving a dowry is an obligation in Islam, and the husband must give it voluntarily and is part of the marriage contract process. A dowry is a mandatory gift given by a prospective husband to a prospective wife as a form of a husband's sincerity and sincerity towards his wife to create feelings of love from both of them. The form of dowry given to women is in the form of goods or services. Religion also does not determine the maximum or minimum amount of dowry that a prospective husband must give to his wife. Therefore, due to differences in a man's ability to give the dowry.